The Influence of Entrepreneurship Education on TheEntrepreneurial Intention of Students Major in EconomicManagement in Higher Vocational Colleges - Yanling, Yun; Hock, Kway Eng (South Asian Journal of Social Sciences and Humanities, 2023)
This research examines the impact of entrepreneurship education on entrepreneurial attitude and intention among students majoring in economic management in higher vocational colleges. The study reveals that entrepreneurship education has a positive and significant effect on both entrepreneurial attitude and intention. Furthermore, it finds that entrepreneurial attitude serves as a mediating factor in the relationship between entrepreneurship education and entrepreneurial intention. The research also highlights significant gender differences, indicating that male students exhibit higher average levels of entrepreneurial intention compared to female students. However, there were no discernible gender variations in entrepreneurial tendencies. Those with and without business experience demonstrate distinct disparities in entrepreneurial ambition, with those with business experience exhibiting stronger entrepreneurial intention.
Keywords: Entrepreneurship education; entrepreneurial attitude; entrepreneurial intention